(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
A legal framework for “demilitarizing” institutions in the first Eritrean Colony: the (unexecuted) legal drafts of counselor Piccolo Cupani The research examines, through a historical-legal and historical-institutional methodology, the draft bills formulated by Vincenzo Piccolo Cupani to demilitarize the legal framework of the Eritrean Colony. Piccolo Cupani, a magistrate in the Kingdom of Italy, was appointed by Francesco Crispi, Prime Minister in 1890, colonial Counselor for Internal Affairs in the administration of the new colony. The resistance from military authorities, however, prevented these drafts from being enacted.